Low-temperature amorphous oxide semiconductors for thin-film transistors and memristors: physical insights and applications - Martins, Jorge de Souto (2022)
While amorphous oxides semiconductors (AOS), namely InGaZnO (IGZO), have found market application in the display industry, their disruptive properties permit to envisage for more advanced concepts such as System-on-Panel (SoP) in which AOS devices could be used for addressing (and readout) of sensors and displays, for communication, and even for memory as oxide memristors are candidates for the next-generation memories. This work concerns the application of AOS for these applications considering the low thermal budgets (< 180 °C) required for flexible, low cost and alternative substrates. For maintaining low driving voltages, a sputtered multicomponent/multi-layered high-κ dielectric (Ta2O5+SiO2) was developed for low temperature IGZO TFTs which permitted high performance without sacrificing reliability and stability. Devices’ performance under temperature was investigated and the bias and temperature dependent mobility was modelled and included in TCAD simulation. Even for IGZO compositions yielding very high thermal activation, circuit topologies for counteracting both this and the bias stress effect were suggested. Channel length scaling of the devices was investigated, showing that operation for radio frequency identification (RFID) can be achieved without significant performance deterioration from short channel effects, which are attenuated by the high-κ dielectric, as is shown in TCAD simulation. The applicability of these devices in SoP is then exemplified by suggesting a large area flexible radiation sensing system with on-chip clock-generation, sensor matrix addressing and signal read-out, performed by the IGZO TFTs. Application for paper electronics was also shown, in which TCAD simulation was used to investigate on the unconventional floating gate structure. AOS memristors are also presented, with two distinct operation modes that could be envisaged for data storage or for synaptic applications. Employing typical TFT methodologies and materials, these are ease to integrate in oxide SoP architectures.